Deficiencia de Boro en Plantaciones de Pinus radiata D. Don en Chile II. Principales Causas y Corrección - Schlatter, Juan S.; Gerding S., Victor (Bosque (Valdivia), 1985)
The present work review's the knowledge about cause, effect and correction of the boron deficiency in Pinus radiata plantations. These compilation is focused to the Chilean situation and it can be emphasized in the following aspects: the detection and correction of boron deficiency are methodologicaly known: It is recommended to apply a preventive fertilization before pine plantations are 2 years old within soils prone to the deficiency. There is a high relation between boron availability and soil fertility. Forest management tend to mantain or improve soil fertily in order to solve the problem in the long term.